Bioethics and bio-juridical ethics from the perspective of Stomatological Law - Dadonim Vila Morales (Editorial Ciencias Médicas, 2015)
Introduction: Stomatological Lawis the branch of the Medical Law studying patient-stomatologist relation, as well as the ethical behavior of the individual in relation to the stomatological activity in its context, having as purpose countersign in law the juridical doctrinal institutions that normalize this relation, on a scientific and ethical, contemporary and cultural postulate. Objectives: describe the morality and the ethics as social values, as well as establishing the relations between the stomatological ethics, the stomatological bioethics and the Stomatological Law, and conceptualizing bio-juridical ethics. Main comments: the stomatological bioethics is the branch of the medical bioethics that, from its transdisciplinary conception, integrates and applies all possible areas of knowledge, from the philosophical focus of the dialog of knowledge, to safeguard the best ethical values applied to all the dimensions of the stomatological practice with integrative social vision, towards propitiating and promoting health. Global considerations: the policy-setting character of the Medical Law reigns on the bioethics, regulating the ethical dilemmas in the practice of medicine and stomatology, by means of a set of ruling dispositions that guarantee juridically the health-based practice.